Effects of type of lesion and trimming on short-term behavior of grazing dairy cows - Eduardo Augusto da Cruz; Vivian Fischer; Lorena Teixeira Passos; Gabriela Caillava da Porciuncula; Marcelo Tempel Stumpf; Daíse Werncke; Carolina da Silva dos Santos (Revista Brasileira de Zootecnia)
ABSTRACT This study aimed to investigate how type of hoof injury and corrective trimming alter the behavior of dairy cows. Thirty-four lactating Holstein and Jersey cows were used. They were scored for lameness score on days –2 and 6, before and after trimming and treatment, respectively, using a numerical rating system, in which 1 = perfect gait and 5 = severely lame, and had their postural and ingestive behavior evaluated on days –1 and 6 before and after trimming and treatment, respectively. Locomotion score was analyzed using t-paired test and behavioral data were analyzed by univariate variance analysis with cows as the experimental units, according to a completely randomized design with repeated measurements. Cows with infectious hoof diseases spent less time lying down and idling, but more time standing up and feeding at the trough than those with non-infectious hoof diseases. Locomotion score and the proportion of time spent standing decreased one week after trimming and treatment, while time spent lying down increased. Trimming plus treatment and type of hoof diseases do not change ingestive behavior but change postural behavior of dairy cows.